THE RELATIONSHIP OF WORK STRESS AND WORK MOTIVATION TO PERFORMANCE OF BRI JAKARTA KREKOT BANK OFFICE EMPLOYEES - Simbolon , Selvi Ernawati; Josephine Tobing; Frangky Y Sitorus (Fundamental Management Journal, 2021)
Human resources are an important asset in enhancing development within a country. The success of a country can be seen from the quality of human resources related to the production of a country. Human resources are the center of attention and focus for organizations or companies to survive in increasingly fierce competition in the current era of globalization. This research is used to analyze the relationship between work stress and employee performance and to analyze the relationship between work motivation and employee performance at the branch office of Bank Rakyat Indonesia, Jakarta Krekot. Collecting data by distributing questionnaires to 53 employees. Analyzed by Spearman Rank correlation analysis, the data was processed using IBM SPSS version 26. Keywords: Work Stress, Work Motivation, Employee Performance